2016
DOI: 10.15845/jper.v3i1.982
|View full text |Cite
|
Sign up to set email alerts
|

"How can you live without your kids?": Distancing from and embracing the stigma of “incarcerated mother"

Abstract: This article examines how incarcerated mothers constructed moral identities in the face of stigma. Analyzing data from participant observation and 83 in-depth interviews with incarcerated mothers, we show that mothers claimed moral identities by distancing from the stigma of incarceration and/or embracing the identity of incarcerated mothers. Utilizing these strategies, women challenged the stigma of convicted felon/ bad mother and reinforced the assumptions that motherhood is compulsory and should be reserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Therefore, the themes presented are representative only of women who volunteered this information unprompted, which may indicate that they valued their identity as mothers or were in some way grappling with their mothering role and their relationship to their children. It is possible that mothers who did not volunteer this information could have divergent themes from the ones presented herein, although our analysis is reflective of others which purposively sampled incarcerated mothers (e.g., Aiello & McQueeney, 2016;Barnes & Stringer, 2014;Mignon & Ransford, 2012;Moe & Ferraro, 2006). Future research, however, should attempt to address selection bias and social desirability as factors which limit our confidence in the depth and breadth of reported results and create a more multifaceted presentation of how incarcerated women can and do mother.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, the themes presented are representative only of women who volunteered this information unprompted, which may indicate that they valued their identity as mothers or were in some way grappling with their mothering role and their relationship to their children. It is possible that mothers who did not volunteer this information could have divergent themes from the ones presented herein, although our analysis is reflective of others which purposively sampled incarcerated mothers (e.g., Aiello & McQueeney, 2016;Barnes & Stringer, 2014;Mignon & Ransford, 2012;Moe & Ferraro, 2006). Future research, however, should attempt to address selection bias and social desirability as factors which limit our confidence in the depth and breadth of reported results and create a more multifaceted presentation of how incarcerated women can and do mother.…”
Section: Strengths and Limitationsmentioning
confidence: 88%
“…These implicit biases are typically grounded on deeply held cultural beliefs about acceptable behavior for women, and stereotypes about the types of women who become embroiled in violent relationships and engage, even tangentially, in criminalized behavior (Keitner, 2002;Snider, 2003;Wattanaporn & Holtfreter, 2014;Weare, 2013). Stereotyping and discrimination are amplified for pregnant women and mothers of young children, who are often labeled unfit, indifferent, and neglectful mothers (Aiello & McQueeney, 2016;Kauffman, 2001;Teather, Evans, & Sims, 1997). Incarcerated mothers, therefore, are subjected to additional layers of scrutiny and judgment; they are framed not simply as "criminals" or "deviants," but as selfish, thoughtless women who made reckless decisions which did not preference their children or honor their duty as mothers (Allen et al, 2010;Berry & Eigneberg, 2003;Chesney-Lind, 2017;Moe & Ferraro, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the midst of a discussion about birthday cake, one focus group participant fretted about her son's upcoming first birthday. This exchange and the mother's concern reflected the fragility of mothering from behind bars, a theme that has been demonstrated in past research (Aiello & McQueeney, 2016;Easterling, 2012;Easterling & Feldmeyer, 2017;Enos, 2001). The worry expressed by the mother also indicated her identification with what constituted a good mother, one who would not miss her child's birthday party.…”
Section: Navigating Spoiled Motherhoodmentioning
confidence: 74%
“…At the same time, mothers explicitly recognize and must negotiate the dissonance between competing identities (e.g., "mother" vs. "inmate"). Aiello and McQueeney (2016) found that motherhood was the most valued identity perceived as lost by women during the process of jail incarceration. Furthermore, their findings suggest that the experience of separation from children during incarceration is "an invisible form of gendered punishment" (p. 54).…”
Section: Mothering Behind Barsmentioning
confidence: 99%
“…While eliminating the allowance of physical touch has an uncertain impact on contraband, it has a concrete impact on inmates' and visitors' mental and emotional well-being (Law, 2015). Ample research reveals that forbidding physical contact with visitors can lead to inmate self-harm, inability to develop positive identities and self-esteem (this has been researched explicitly in relation to incarcerated mothers' ability to touch their children), and decreased ability to adapt to society after release (Kaba, et al, 2014;Aiello & McQueeny, 2016;Law, 2015). In an interview with writer and prison abolitionist activist Victoria Law, former Rikers Island prisoner Anthony Collado reflects:…”
Section: No Human Contactmentioning
confidence: 99%